Integrating Group Investigation Method and Local Wisdom to Enhance Students’ Writing Skill - Mimi Mulyani; Puri Bakthawar; Sirajul Munir (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
The integration of local wisdom and teaching method in all language skills are important to preserve the culture and to insert the character values. This notion relates with this study in which the local wisdom and group investigation method are integrated in teaching writing. Group investigation is teaching method that build students’ team work. Besides, the aim of this study is to explore the effect of implementing group investigation method and local wisdom in improving students’ writing skill. The research method used is a quasi-experimental study (one group Pre-test - Post-test). The subject of this study is junior high school students. The results of T-test show that there is a significant difference of students’ writing skill before and after getting the treatment. Besides, integrating group investigation method and local wisdom is more effective to enhance students’ writing skill. Furthermore, this study gives theoretical, practical, and pedagogical implications in teaching writing. The novelty of this study is that this study uses interdisciplinary approach, especially in integrating the local wisdom discourse and group investigation method. The contribution of this study is to the language teachers especially those who concern with writing skills, on how to develop teaching method using cultural approach in creative way